Expression of e-NOS in Human Placentas of Idiopathic Intra Uterine Growth Restriction at Term (Medico Legal Update, 2020)
Endothelial nitric oxide synthase (e-NOS) is a chemical agent that involves in placental angiogenesis. It is conveyed through embryogenesis. In the contemporary study, we intended to examine the character of placental angiogenesis in the progress of intrauterine growth restriction (IUGR) by means of matching the levels of expression of e-NOS in normal-term pregnancy and IUGR placentas. Angiogenesis is one dominant factor in normal embryogenesis and hence the wellbeing of the newborn. The expression of e-NOS was planned using the streptavidin-biotin-peroxidase technique in placental tissues identified as normal (n = 33) and IUGR (n = 33) cases from mothers looking apparently normal. All were chosen at term pregnancy and obtained between 2nd of February of 2018 and 31th of January 2019 at selected hospitals. Outcomes were appraised semi-quantitatively. The expression of e-NOS marker as an immunohistochemistry total score and staining percentage were significantly greater (p < 0.05) in epithelial surface, smooth muscle cells of fetal vessels and the connective tissue terminal villous core of the IUGR placentas when matched with placentas collected from normal pregnancies at term. Encountered placental histochemical changes regarding the expression of the e-NOS angiogenic factor for idiopathic IUGR newborns raised the suspicion of that, it was caused by pure placental factors and could represent further requirement for Nitric Oxide to dilate fetal vessels to optimize functional requirement during placental insufficiency. The noticed Increased expression of e-NOS may be the result of inadequate uteroplacental perfusion supporting the proposal that abnormal angiogenesis plays a role in the pathophysiology of IUGR